Survival differences among freeze-dried genetically engineered and wild-type bacteria. - Israeli, E (1993)
Because the death mechanisms of freeze-dried and air-dried bacteria are thought to be similar, freeze-drying was used to investigate the survival differences between potentially airborne genetically engineered microorganisms and their wild types. To this end, engineered strains of Escherichia coli and Pseudomonas syringae were freeze-dried and exposed to air, visible light, or both. The death rates of all engineered strains were significantly higher than those of their parental strains. Light and air exposure were found to increase the death rates of all strains. Application of death rate models to freeze-dried engineered bacteria to be released into the environment is discussed.